Tacit knowledge about internal marketing in health care institutions - Lozano Ramirez, Ma. Cruz (Cuadernos de Administración, 2022)
The objective of health care institutions is to provide physical, mental and social well-being to the population. To fulfill this mission, they execute administrative processes with their internal stakeholders (doctors, nurses and administrative and contact staff) and external stakeholders (patients and families), promoting a collaborative work environment that contributes to the optimal development of the institution’s human capital. This work environment is known as internal marketing and is motivated by senior management, who, based on the organizational management structure, seek to generate the best working conditions and inspire the development of human capital with the goal of better serving external clients. To explore the impact of these actions in health care institutions, we began by assessing tacit knowledge through the experiences of patients’ relatives. Using this approach, the fundamental objective of the analysis was to explore internal marketing actions in health institutions based on external clients’ (relatives of the patients) experiences regarding equipment and tools for the execution of the work, performance and job satisfaction and to compare the results with the Leonard Berry model. To this end, the methodological design as supported by a literature review and operationalized within the internal marketing variable. Among the main findings, affinity was identified in the dimensions treating the employee like a customer and recognizing the task as a product, employee satisfaction, service-oriented attitudes, perceived quality of services and customer satisfaction in the Berry model. Based on these preliminary results, we concluded that internal marketing in health care institutions has a favorable impact on human capital and that this is supported by the experiences of family members who accompany patients during their hospital stay, who develop emotional bonds through the treatment that is received.